EXPLORING THE ADVENTURE GENRE WITHIN THE MULTIVERSE DIMENSION IN EVERYTHING EVERYWHERE ALL AT ONCE (2022) - Nurul Aulia Permana; Yuhana Puspita (Saksama: Jurnal Sastra, 2025)
Daniel Kwan and Daniel Scheinert’s Everything Everywhere All At Once (2022) offers an innovative reinterpretation of adventure genre conventions by integrating elements of science fiction, absurdist comedy, and existential inquiry. The film reframes adventure not solely as a physical journey across dimensions, but as an emotional and psychological odyssey, centered on the protagonist Evelyn’s internal transformation. Drawing upon John G. Cawelti’s theory of adventure narrative structure, this paper examines how traditional genre patterns are reshaped within a chaotic multiverse framework. Evelyn’s “verse-jumping”—depicted as more than spatial traversal—functions as a symbolic mirror of self-reflection, exposing multiple unrealized paths within her fractured identity. Employing a qualitative research approach and content analysis methodology, the study reveals that the film transcends the conventional ‘save-the-world’ trope to explore deeper themes of self-acceptance, existential pressure, and meaning-making within ordinary life. Ultimately, Everything Everywhere All At Once revitalizes the adventure genre, presenting it in a form that resonates with contemporary narrative complexity and emotional depth.